A legal and Shariah analysis on the Shariah compliant company's obligation to pay zakat in Malaysia - Nazri Ramli
Paying zakat is one of the five pillars of Islam and paying zakat on urudh al-tijarah (business inventory) is a religious obligation upon all Muslim traders. In contemplating its objectives of economic and social responsibility to zakat recipients, numerous international fatwas of Muslim countries resolved that companies are also obligated to pay zakat on the basis of its analogous resemblance to the khultah (mingling-property) principle and Islamic business entities of sharikah and mudharabah. In Malaysia, this view was adopted by the Fatwa Councils in respective states which resolved that companies registered under the Companies Act 2016 are obligated to pay zakat. Nonetheless, the direct imposition of the fatwas to corporations has legal implications from both civil and Shariah laws in Malaysia due to the fact that as a body corporate, the company is distinct from its members and exists only by the contemplation of law as a fictitious and non-religious entity. Therefore, this thesis aims to analyse the obligation of company as an artificial legal entity to pay zakat obligatorily. This research applies doctrinal analysis, whereby the doctrine of the artificial legal personality of corporation under the common law, and the theory of al-dhimmah under the Shariah are analyzed. Discussion in this thesis focusses on the application of the fatwas and views of contemporary scholars on the obligation of corporations as artificial persons to pay zakal. As for data collection, this research resorted to data from primary and secondary sources in law as well as interview with legal and Shariah experts. The data from the primary sources consist of legal statutes and law cases, whereas the data from secondary sources include law books, journals, newspapers, articles and reports, conference proceedings and other relevant legal documents. All of the above data were gathered through library research from legal databases, websites or written materials. The research found that the fatwa which imposed an obligation on companies to pay zakat gives rise to many legal implications due to the dichotomy and fundamental principle that companies are fictitious entities and have no religion. This research also found that the resolution made by members of the Fatwa Council that companies are obliged to pay zakat was based on the analogy that companies are similar to sharikah and khultah principle. This resolution is not correct as a company is distinct from its members in the aspects of ownership and liability, whilst sharikah and khultah connotes a collective association of all its partners and there is no separation between the entity and its partners. In general, the fatwa which imposes obligation on companies to pay zakat can only be executed if there are modifications to the existing legal corporate structures. The imposition of fatwa on companies in Malaysia to pay zakat is only possible if there is a modification to the existing company law by adopting the concept of sharikah and khultah.